SOME OBSERVATIONS ON THE SPERMATOZOA OF AQUARIUM FISHES - Rajagopal, S; Reddy, P Sitarami (Indian Journal of Fisheries, 2011)
The present paper deals with the morphology and biometry of the spermatozoa of four types of aquariumfishes viz., koi carp (Cyprinus carpb), black shark (Morulius chrysophakadion), marigold platy (Xiphophorusmaculatus) and delta black guppy (Lebistes reticulatus) for the first time. The shape of the head, middlepiece and tail have been described along with the biometric data. A comparative account of thespermatozoa of the four types of aquarium fishes has been incorporated